A U‐shaped association between serum albumin with total triiodothyronine in adults. Issue 6 (6th May 2022) - Zhang, Ya; Xie, Ruijie; Ou, Jun
Abstract: Background: Thyroid dysfunction is a common thyroid disorder in our life and its symptoms are non‐specific, therefore the diagnosis of thyroid dysfunction is important for patients. Albumin (ALB) can carry thyroid hormones to their sites of action as a way to achieve rapid delivery of thyroid hormones to the tissues. The purpose of this study was to investigate the relationship between serum ALB levels and total triiodothyronine (TT3) in adults. Methods: Data from the 2007–2012 National Health and Nutrition Examination Survey (NHANES) were used to examine the association between ALB and TT3 using multivariate logistic regression models. Fitting smoothed curves and generalized weighted models were also used. Results: The analysis included a total of 7933 participants that we found an independent positive relationship between ALB and TT3 among participants [0.006 (0.003, 0.009)]. In men, there was a significant positive correlation between ALB and TT3, whereas in women ALB and TT3 suggested a significant negative correlation. Moreover, our study revealed that the independent association between the levels of ALB and TT3 was significant in Non‐Hispanic White, but not in Non‐Hispanic Black. Notably, we found a U‐shaped association between ALB and serum TT3 in total participants (inflection point for ALB: 41 g/L) and females after adjusted covariates (inflection point for ALB: 46 g/L). Conclusions: We found a U‐shaped relationship between serum ALB and TT3 with infection point at 41 g/L for ALB, which may provide a reference for future screening in adults with thyroid dysfunction. Abstract : This study found a positive relationship between ALB and TT3 among most adults. Notably, we found a U‐shaped association between ALB and serum TT3 in participants, especially in females (inflection point for serum albumin levels: 46 g/L), which may provide a reference for guiding treatment and screening in adults with thyroid dysfunction including subclinical symptoms.